2013
DOI: 10.1155/2013/726820
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Ternary Mixture of Aspirin, Atorvastatin, and Clopidogrel by Chemometric-Assisted UV Spectroscopic and Liquid Chromatography Methods

Abstract: Two chemometrics-assisted UV spectrophotometric methods were proposed for the resolution of ternary mixtures without any chemical pretreatment. The first method is based on modification of H-point standard addition method which permits simultaneous analysis of three species from a unique calibration set by making the simultaneous addition of the three analytes. Quotient between the spectra of aspirin, atorvastatin, and clopidogrel was obtained and the results showed that simultaneous determination of aspirin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Upon the literature survey, a few spectrophotometric methods have been proposed for the analysis of ASP, CLP, and ATV or ROS in pharmaceutical preparations 11–16 . Besides, few liquid chromatography with tandem mass spectrometry (LC‐MS/MS) and high‐performance liquid chromatography (HPLC) methods have been proposed for the analysis of ASP, CLP, and ATV or ROS in pharmaceutical preparations 17–21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon the literature survey, a few spectrophotometric methods have been proposed for the analysis of ASP, CLP, and ATV or ROS in pharmaceutical preparations 11–16 . Besides, few liquid chromatography with tandem mass spectrometry (LC‐MS/MS) and high‐performance liquid chromatography (HPLC) methods have been proposed for the analysis of ASP, CLP, and ATV or ROS in pharmaceutical preparations 17–21 …”
Section: Introductionmentioning
confidence: 99%
“…10 Upon the literature survey, a few spectrophotometric methods have been proposed for the analysis of ASP, CLP, and ATV or ROS in pharmaceutical preparations. [11][12][13][14][15][16] Besides, few liquid chromatography with tandem mass spectrometry (LC-MS/MS) and high-performance liquid chromatography (HPLC) methods have been proposed for the analysis of ASP, CLP, and ATV or ROS in pharmaceutical preparations. [17][18][19][20][21] The UV absorption spectra of ASP, CLP, and ATV in mixture (1) and ASP, CLP, and ROS in mixture (2) in distilled water at their nominal concentrations ratio in tablets and capsules show strong overlap (Figures 2 and 3).…”
Section: Introductionmentioning
confidence: 99%
“…Few reports on spectrophotometric methods are also available. [13][14] Till date there is no report available on High-Performance Thin-Layer Chromatographic (HPTLC) method for the estimation of vitamin B1, B2 and B6…”
Section: Figure 1 Structure Of Drugsmentioning
confidence: 99%
“…CLP is official in the United State Pharmacopoeia (USP) (3). Literature survey revealed that many HPLC methods have been published for its determination either alone [18][19][20][21] or in combination with other drugs [22][23][24][25][26]. Assay of synthetic mixture of RIV and CLP has been described previously using HPLC method with UV detection at 240 nm [17], but it could not be used for determination of rivaroxaban in plasma.…”
Section: Introductionmentioning
confidence: 99%